1984
DOI: 10.1002/pssb.2221260232
|View full text |Cite
|
Sign up to set email alerts
|

Galvanomagnetic Effects of Bismuth in Non‐Quantising Magnetic Fields. Pseudo‐Parabolic Model

Abstract: The non-parabolicity of the L-point carriers and the temperature dependence of the band structure are incorporated in a model for the transport properties of bismuth. Results are given for elements of the resistivity tensor versus magnetic field a t temperatures around 80 and 300 K. A comment is made to the papers of Gitsu et al.La non-parabolicit6 des porteur au point L et la dependance de temperature de la structure des bandes sont incorporees dans un modde pour les phenombnes de transport dans le bismuth. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…2 and from 77 to 300 K by Ref. 16. The mobilities, noted for the light electrons L (T), for the heavy electrons H (T), and for the holes v(T), are functions of the longitudinal masses.…”
Section: ͑6͒mentioning
confidence: 93%
See 1 more Smart Citation
“…2 and from 77 to 300 K by Ref. 16. The mobilities, noted for the light electrons L (T), for the heavy electrons H (T), and for the holes v(T), are functions of the longitudinal masses.…”
Section: ͑6͒mentioning
confidence: 93%
“…For comparison, the calculated values of k Fc for the heavy and light electrons and for the holes in bulk Bi are also shown in Fig. 13, using the temperature dependence of the carrier density 2, 16 and assuming that the band structure has no temperature dependence below 77 K. 17,18 A comparison between bulk and wires in Fig. 13 shows that the measurements on the 48-and 70-nm wires do give the right order of magnitude, but that there is more temperature dependence to the value of k Fc in the wires than in the bulk.…”
Section: ͑6͒mentioning
confidence: 99%
“…In the semimetal Bi, however, the two different dependencies coexist because of its small carrier concentration (2.7 Â 10 17 -3.0 Â 10 18 cm À3 at 2-300 K). 14,16,28,30 In bulk Bi, the change in carrier mobility is reportedly larger than that of the carrier concentration by more than two orders of magnitude over the temperature range 77-300 K. 14,[65][66][67] Therefore, the mobility contribution dominates that of the concentration, resulting in a monotonic metallic temperature dependence of the resistance in bulk Bi, as shown in Fig. 10.…”
Section: Electrical Conductivitymentioning
confidence: 97%
“…The temperature dependence of the electrical resistance of Bi CNWs is generally the result of the interplay of charge carrier density and mobility, which show contrasting variations with temperature. 6,10,13,46,47,[49][50][51][52] For the 230 nm Bi CNW sample, the increase in resistance with decreasing temperature reflects the dominant contribution of the temperature change in carrier density, since their mobility weakly depends on temperature because of scattering processes dominated by NW surfaces and grain boundaries. On the contrary, the increase in resistance following a temperature decrease is much less pronounced for small diameter Bi NWs and a weak metallic behavior appears below T ∼ 100 K. It has been suggested that the quantum confinement leading to the semi-metal-semiconductor transition when the diameter is less than 50 nm is generally masked by the increasing importance of surface carriers as the diameter decreases.…”
Section: Electrical and Thermoelectric Measurementsmentioning
confidence: 99%